SINGULARITIES AND COMPUTER ALGEBRA - CRISTOPH LOSSEN; GERHARD PFISTER (U K CAMBRIDGE UNIVERSITY PRESS, 2006)
A collection of articles giving overviews and open questions in singularities and their computational aspects.
Keywords: SINGULARITIES-MATHEMATICS -- ALGEBRIC GEOMETRY -- COMPUTER SCIENCE-MATHEMATICS